2008
DOI: 10.1095/biolreprod.107.066860
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Molecular Chaperone, Heat Shock Protein 1 (Chaperonin 10), in the Reproductive Tract and in Capacitating Spermatozoa in the Male Mouse1

Abstract: Mammalian spermatozoa must undergo epididymal maturation in the male reproductive tract and capacitation in the female tract before acquiring the ability to fertilize an oocyte. Previous studies from our laboratory have demonstrated a causal relationship between capacitation-associated surface phosphotyrosine expression and the ability of mouse spermatozoa to recognize the oocyte and engage in sperm-zona pellucida interaction. Our previous analyses of the surface phosphoproteome of capacitated murine spermatoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…Specifically, HSPs are critically important during spermatogenesis and the posttesticular maturation of mammalian spermatozoa that aberrant expression is associated with spermatogenesis arrested and defects in sperm function (Dun et al 2012). The stage-specific expression pattern displayed by HSPs during spermatogenesis indicates that HSPs are involved in germ cell development (Feng et al 2001, Huo et al 2004, Asquith et al 2005, Terada et al 2005, Held et al 2006, Adly et al 2008, Walsh et al 2008, Lachance et al 2010, Ji et al 2012. In addition, HSPA1B has been implicated in fertilization and embryo development (Neuer et al 2000, Matwee et al 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, HSPs are critically important during spermatogenesis and the posttesticular maturation of mammalian spermatozoa that aberrant expression is associated with spermatogenesis arrested and defects in sperm function (Dun et al 2012). The stage-specific expression pattern displayed by HSPs during spermatogenesis indicates that HSPs are involved in germ cell development (Feng et al 2001, Huo et al 2004, Asquith et al 2005, Terada et al 2005, Held et al 2006, Adly et al 2008, Walsh et al 2008, Lachance et al 2010, Ji et al 2012. In addition, HSPA1B has been implicated in fertilization and embryo development (Neuer et al 2000, Matwee et al 2001.…”
Section: Discussionmentioning
confidence: 99%
“…One cauda epididymidis was removed from each animal from control and heat-treated groups, then blotted on filter paper and placed in equal volume of 500 µL prewarmed modified Biggers, Whitten and Whittingham (BWW) medium [19]. Spermatozoa were extruded by retrograde perfusion of BWW into the vas deferens after making a small incision in the cauda epididymidis [20]. They were allowed to disperse into the medium in an incubator, maintained at 37ºC with 5% CO2 in air, for 10 min.…”
Section: Collection Of Spermatozoamentioning
confidence: 99%
“…This turned out to be the molecular chaperone, chaperonin (Cpn)/heat shock protein (Hsp)10, a mitochondrial protein (Cavanagh and Morton 1994). Co-incidentally, both Hsp10 and the co-chaperone Hsp60 are now implicated as cell surface proteins essential for the capacitation of sperm, revealing a 'prior role' for these proteins in pregnancy (Walsh et al 2008). However, it was Hightower, 1 year after the description of the mechanism of action of Hsp60, who first revealed that a molecular chaperone, in this case Hsp70, was released by cells (Hightower and Guidon 1989).…”
Section: Secreted and Extracellular Molecular Chaperonesmentioning
confidence: 99%